THE EFFECT OF FARMER BUSINESS SCHOOL ON HOUSEHOLD WELFARE: EVIDENCE FROM COCOA FARMERS IN ATWIMA NWABIAGYA NORTH DISTRICT, GHANA - Aborah, Rosalyn; Appiah, Patrick; Tham-Agyekum, Enoch Kwame; Ankuyi, Fred; Amankwa, Kwadwo; Andivi Bakang, John-Eudes; Nimoh, Fred (Applied Studies in Agribusiness and Commerce, 2023)
Farmer Business School (FBS) is an educational programme aimed at improving the knowledge and skills of farmers in various aspects of agriculture, including financial management and marketing. The purpose of the paper is to examine the effect of FBS on household welfare among cocoa producers in the Atwima Nwabiagya North District of Ghana.  Data was collected from a sample of 330 cocoa farmers, 200 of which participated in the FBS programme and 103 who did not. The study employed a range of statistical techniques to investigate the effect of FBS on cocoa growers, thus, independent samples t-test, binary probit model, Kendall's Coefficient of Concordance and perception index. The results of the study suggest that involvement in the FBS programme has a positive significant influence on household welfare. Cocoa farmers who participated in the programme experienced a significant increase in income and yield, as well as improved overall well-being against those who didn't take part. The research's findings offer evidence that FBS programmes can play a vital role in enhancing the welfare of farmers, particularly in developing nations where agricultural livelihoods play a crucial role in economic growth and poverty reduction. The study highlights the importance of investing in education and training programmes for farmers to improve their skills, knowledge, and overall well-being.